MODEL PEMBENTUKAN KULTUR AKHLAK MULIA SISWA SEKOLAH MENENGAH PERTAMA DI INDONESIA - Ajat Sudrajat (Universitas Negeri Yogyakarta, 2010)
This research was aimed to find a model of culture development of noble characters at several Indonesian schools with sample schools in Java. The data was obtained through interviews, questionnaires, documentation, and FGD. The results showed that a good model should be developed in building cultures of noble characters for junior high school students in Indonesia consisting of the following: Schools should formulate vision, mission, and directions leading to building noble character cultures at school; there were supports with the same perception among school citizens; there was a high consciousness for all school citizens; there was an assertive policy from the headmaster; there were clear and assertive programs and regularity of schools; there were accustoming values of noble characters within daily activities at school both religious and common ones; there were supports from all parties in realizing noble character cultures at school; there were exemplaries from teachers and employees; there was a synergy among three education centres, and there were rewards and punishments